Complete Skin Clearance is Associated with the Greatest Benefits to Health-Related Quality of Life and Perceived Symptoms for Patients with Psoriasis - Matthias Augustin; Alice B. Gottlieb; Mark Lebwohl; Andreas Pinter; Richard B. Warren; Luis Puig; Rhys Warham; Jérémy Lambert; Susanne Wiegratz; Balint Szilagyi; Andrew Blauvelt (Adis, Springer Healthcare, 2024)
Abstract Introduction With newer biologics, the achievement of complete skin clearance has become an attainable treatment goal for patients with plaque psoriasis. We evaluate how improvements in Psoriasis Area and Severity Index (PASI) responses, particularly at incremental improvements approaching complete skin clearance (PASI 100), translate into improvements in health-related quality of life (HRQoL) and patient-perceived symptoms. Methods Data from the BE RADIANT phase 3b trial (NCT03536884) and its open-label extension (OLE), pooled across all study visits and treatments over 16 weeks (randomised patients) and 2 years (patients entering the OLE), were analysed using mixed-effects logistic regression models. Proportions of patients achieving a Dermatology Life Quality Index (DLQI) of 0/1, DLQI item scores of 0, and Psoriasis Symptoms and Impacts Measure (P-SIM) item scores of 0 for itching, scaling, and skin pain at specific PASI improvement levels were estimated. Results Seven hundred and forty-three patients were randomised to treatment; 654 entered the OLE. Using 16-week pooled data, there were incremental improvements in the proportions of patients estimated by our model to achieve DLQI 0/1 with PASI 100 compared with 95% (PASI = 95%) and 90% (PASI = 90%) improvements in PASI (93.0%, 89.3%, and 83.8% achieving DLQI 0/1, respectively). Estimated proportions achieving DLQI item scores of 0 had the greatest increases at higher PASI improvement levels for Items 1 (itchy, sore, painful, or stinging skin), 2 (embarrassment), and 4 (choice of clothing). Estimated proportions of patients achieving P-SIM = 0 were also higher for PASI 100 (itching: 61.7%; scaling: 82.2%; skin pain: 96.9%) than for PASI = 95% (50.8%; 72.3%; 95.7%) and PASI = 90% (39.8%; 59.5%; 94.0%). Similar benefits of incremental PASI improvements were estimated using 2-year data. Conclusions Complete skin clearance translated into the greatest benefits to HRQoL and patient-perceived symptoms, over and above skin clearance between 90% and 100%, highlighting the importance of targeting PASI 100 as a treatment outcome for patients with psoriasis. Trial Registration Number NCT03536884. Complete skin clearance is associated with the greatest benefits to health-related quality of life and perceived symptoms for patients with psoriasis: KeyResults and Conclusions (MP4 72828 kb)